Modelling and simulation of working conditions of transport machines by using of autoregressive models - Leitner, Bohuš; Máca, Jaromír (Univerzita Pardubice, 2004)
Paper is dealing with a new method of modelling and simulation of stationary and nonstationary processes. The method is based on description of processes by AutoRegressive Moving Average (ARMA) Models and their adaptive modifications. This paper presents possible application of ARMA models for modelling and simulation the real working process of typical working conditions of a truck.
Keywords: dopravní provoz; Modelování; simulace; stochastické systémy; nestacionární procesy